ANALISIS PENDAPATAN DAN PROFITABILITAS PADA PETERNAKAN SAPI PERAH SUMBER MULYA DI KABUPATEN KEPAHIANG - Dadang Suherman; Sutriyono; Riko Herdiansah (Wahana Peternakan, 2021)
ABSTRACT The study was purposed to find out income and profitability was achieved by a Sumber Mulya dairy farm. Research was held in July – Agust 2018 in Sumber Mulya dairy farm Kepahiang. The methods used in this research is case study method. Primary Data obtained through interviews with the respondents and recording. Data obtained for time 12 months on technical aspects and financial data covering production costs, data revenue, income data, the amount of data the data the amount of milk production and livestock lactation. Secondary data retrieved from the data contained in these farms. Data analysis used analysis formulas use income and profitability ratios. The result showed that Sumber Mulya Dairy cattle farm was net incomeaverages per month is Rp. 5,427,176,91 with the number of 7.00 averagecows lactation flat tail. Total cost per month of Rp.10,032,823.29 Profitability achieved by the company said 10,78% profitable because the value of profitability is greater than the interest rate a bank of 4.35%. Key word : income, dairy farm, profitability, dairy farm, milk production